Pelatihan Pemrograman Visual dengan Scratch untuk Siswa SD Negeri Sawah Panggang - Vittalis Ayu; Bambang Soelitisjanto; Henricus Agung Hernawan; Tjendro (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Thinking critically about problems is one of the high goals of education. From a young age, we must learn to think logically about problems and find appropriate solutions to them. As an educational institution, primary school is not only a place where students acquire teaching materials, but also where they develop critical thinking and become accustomed to adapting to the fast-paced development of the world. One of his ways of developing logical thinking, especially in his SD Negeri Sawah, is by teaching his students basic programming skills. This allows students to approach issues in a more structured way. Therefore, Sanata Dharma University Faculty of Science and Engineering, considering the problems of the campus environment, is holding training for students to be able to visually understand the basics of programming as a concern of the academic world. Practice thinking logically. Training presentations are designed like his Scratch games, making students more interested in learning to solve problems. This activity he successfully carried out in two phases. Beginner and advanced classes at Sawah Panggang Primary School will be held offline. Through this activity, some of the students were able to explore more and be more courageous while working on the assignment.